The Effectiveness of Partner Reading Strategy on Students Reading Comprehension - Khilma Aufifil Izzati (Universitas Pahlawan Tuanku Tambusai, 2023)
Reading is considered a crucial skill for English as a second language learners, as it involves the integration of information from a text with prior knowledge to comprehend meaning. However, students often encounter challenges in reading comprehension, displaying varying proficiency levels and difficulties in grasping the content and significance of the material. To address this, the researcher employed a quantitative quasi-experimental design in the study. The findings revealed significant posttest results for both the experimental and control groups, with p-values below the 0.05 threshold. Notably, the experimental group exhibited a more substantial increase in mean posttest scores compared to the control group. As a result, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was supported. Specifically, the experimental group achieved a mean score of 79.06 on the posttests, while the control group attained a mean score of 68.75. These outcomes indicate that the experimental group, which received instruction through the partner reading strategy, outperformed the control group, which utilized the individual reading strategy. Consequently, there exists a significant disparity in reading skills between students instructed using the partner reading strategy and those taught with the individual reading strategy.